BRAND AWARENESS STRATEGY AS A COMMUNICATION MEDIA IN INCREASING MSMEs PRODUCT SALES - Husriadi, Muh. (Journal of Finance, Economics and Business, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the economy, but many face challenges in increasing brand awareness to increase product sales. This study aims to analyze the role of brand awareness in increasing MSME product sales, as well as exploring effective strategies for building brand awareness through social media and storytelling. The method used in this study is a qualitative approach with in-depth interviews with MSME owners. The results of the study indicate that strong brand awareness increases consumer trust and encourages increased purchases. Social media, especially with a storytelling approach, has proven to be an effective and low-cost channel for increasing brand awareness. This study also highlights the importance of utilizing social media appropriately to optimize MSME marketing results with limited budgets. The implications of this study provide insights for MSMEs in developing more effective digital marketing strategies, as well as offering contributions to the development of marketing theory in the context of MSMEs.